MOTIF PARA PENGGUNA MEDIA ONLINE OLX (ONLINE EXCHANGE) DALAM PEMASARAN BARANG BEKAS DI KOTA PEKANBARU - Dedi Samsuddin Efan Saputra; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The development of the internet makes a lot of online media have emerged and are increasingly popular among the people.New lifestyle offered internet marketing online, one of the online media site that provides marketing services of goods is OLX.co.id (Exchange Online), in which people in Pekanbaru using the media as a means of buying and selling used goods. The purpose of this study is to find out the motives of the users of online media OLX in marketing used goods, meaning OLX users of online media in the marketing of used goods, and the communication process OLX users of online media in the marketing of junk in Pekanbaru.In this study the authors used a qualitative research method with a phenomenological approach. Data collection techniques are grouped through observation, interviews and documentation. Informants in this study of 10 people were taken by purposive sampling techniques, respectively 5 5 sellers and buyers of used goods online OLX mediated. Interactive data analysis model the researchers use to describe the results of research into techniques for data analysis and data validity checking researchers used a technique extension of participation and triangulation.The results showed that the motive OLX users of online media in the marketing of junk in the city of Pekanbaru is because motive motive convenience, comfort motif and motif profitable. Meanwhile, in order to motive security, finance, and low prices. Then the meaning of online media OLX by users in marketing junk OLX significantly positive that can bring together between sellers and buyers, OLX makes it easy to sell and buy used, OLX as a source of information goods. While the negative meanings which can OLX fraud. Furthermore, the communication process OLX users of online media in the marketing of junk in the city of Pekanbaru is advertising, feedback and transactions. The nice thing is to feel fun, quality is good stuff, quickly sold out and a lot of users. While the unpleasant things that seem indifferent, annoyed, and the clan is not appropriate.Key word : Motif, online media, marketing